Design of interactive learning courseware for iterative algorithms - Tan, Kris Hong-Wei (2018)
E-learning has greatly increased its popularity in most area of educations and the advantages it provides have shown greatly in both improvement a student and delivering courses in the modern age. Understanding how the world have transform in getting the information from physical books to currently in internet E-book. Education must keep up with the pace of advancement and many platforms are available to assist in creating a good course-ware. One learning management system to consider would be Moodle, as it gained recognitions across the world. Moodle’s documentation on its capabilities has been constantly improving as receiving feedbacks from its great pool of users. Moodle great advantage of it being open source which means freely available for users to develop their course-ware by downloading the packages online. Moodle has functions and features ready for users to start their own course-ware, this paper focuses mainly on the basic component that Moodle provide to support a course-ware and its gamification feature to enhance students’ experience in learning.